Density functional theory and Ab Initio Calculations of the Heats of Formation of Pyrrole and Furan Oligomers: Progress Report - V. BANTACULO, ROLANDO; C. ALGUNO, ARNOLD; M. VEQUIZO, REYNALDO; B. MUNOZ, MARIS; F. FERNANDEZ, MARVIN JOSE; MIYATA, HITOSHI; W. IGNACIO, EDGAR; M. BACALA, Ph.D., ANGELINA (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
Novel conducting polymers have attracted a great deal of attention among researchers because of their promising use as biosensors, organic semiconductors and other popular applications. Requirements of energy efficiency and environmental impact of energy combustion relate to fundamental quantities such as heats of formation of these compounds. However experiments measuring such quantities are not trivial and only few results have been reported. This lack of experimental information can be surmounted by resorting to reliable computational models which will also lead to expansion to new classes of compounds.In this study the heats of formation of polyfuran and polypyrrole were estimated computationally using ab initio G2(MP2) quantum mechanical protocol and density functional theory (B3LYPI6-311 +G**) levels. Heats of fornation of polyfuran and polypyrrole are calculated with an accuracy of better than ±3 kcal/ mol by using the total energy calculated.